Technology helping citizens to express their needs and improve their neighborhood - Kopáčková, Hana; Komárková, Jitka; Jech, Jakub (IEEE (Institute of Electrical and Electronics Engineers), 2019)
Suitable technologies support an effort of citizens to improve their neighbourhood e.g. by reporting problematic issues on a public infrastructure. Citizens are able to identify problematic issues in their environment faster than local governments because they live in a particular place and they are interested in the quality of their life. A citizen reporting tool (CRIsPI) should provide an easy way of reporting problems (issues), seeing already reported issues and seeing feedback. Various tools are used in the Czech Republic: phone, e-mail, Web form, WebGIS, and mobile applications. Case study evaluates penetration of CRIsPI tools in the Czech Republic in July 2018 among municipalities over 1 000 inhabitants. It provides both a detail view in a form of maps and basic descriptive statistics. E.g. all municipalities over 50 000 inhabitants provide at least one CRIsPI tool to inhabitants. Several municipalities provide a combination of more tools. Small municipalities more frequently provide phone or e-mail communication or a Web form only.
Technologie, které pomáhají lidem vyjádřit své potřeby a vylepšit prostředí v sousedství
Keywords: citizen reporting; eParticipation; CRIsPI tools; WebGIS; mobile applications; hlášení občanů; e-participace; nástroje hlášení závad CRIsPI; Webové GIS; mobilní aplikace